Desenvolvimento experimental de uma bancada para estudo da dinâmica de sistemas rotativos - Souza, Elisson David Rebouças de (Universidade Federal Rural do Semi-Árido, 2019)
Rotating machines, when in operation, exert some dynamic efforts that propagate to the parts that will support them, such efforts are duly considered in the design of the project, but several factors during assembly or use may lead to undesirable behaviors, such as misalignment or imbalance, thus causing various damages to the shaft / rotor assembly or even to other components that are interconnected to the system. The objective of the present work is to develop an experimental bench so that it can provide a better understanding of the phenomenon of mechanical vibration in rotary systems. Once started, a way of designing a shaft, rotor and bearing assembly in the system is defined and then doing some analysis and different tests in the bench and raising several results in the different ways of submitting the system to the tests, in order to generate practical and analytical analyzes and also show possible approximations of the real.
Monografia
Keywords: Maquinas rotativas; Rotor; Eixo; Amplitude de vibração; ENGENHARIAS::ENGENHARIA MECANICA